Fostering Children's Learning Through Effective Communicative Strategies in English Reading Comprehension: Insights from Primary Schools in Mubi North, Adamawa State, Nigeria - Adepoju, Adetokunboh Abayomi; Linake, Manthekeleng Agnes; Nisak, Winda Khoirun (Martabat: Jurnal Perempuan dan Anak, 2024)
Reading is the cornerstone of effective learning, forming the foundation for academic success in the classroom. However, achieving meaningful learning outcomes depends heavily on the communicative strategies employed by teachers during reading instruction. This study explored the communicative strategies utilized by teachers in English reading comprehension lessons across selected primary schools in Mubi North Local Government Area, Adamawa State. Through a convenient sampling method, the study engaged seven head teachers and twenty-one teachers, employing two research instruments: a twenty-item, four-point Likert scale questionnaire and a four-item open-ended questionnaire. The findings revealed that teachers predominantly employed constructive communicative strategies to enhance reading comprehension. However, challenges such as overcrowded classrooms and external disruptions hinder optimal teaching and learning processes. The study emphasizes the need for targeted interventions to mitigate these barriers, ensuring a more conducive environment for effective reading instruction.